Pitch enhancement facilitates word learning across visual contexts - Filippi, Piera; Gingras, Bruno; Fitch, W. Tecumseh (Frontiers in Psychology, 2014)
This study investigates word-learning using a new model that integrates three processes: a) extracting a word out of a continuous sound sequence, b) inferring its referential meanings in context, c) mapping the segmented word onto its broader intended referent, such as other objects of the same semantic category, and to novel utterances. Previous work has examined the role of statistical learning and/or of prosody in each of these processes separately. Here, we combine these strands of investigation into a single experimental approach, in which participants viewed a photograph belonging to one of three semantic categories while hearing a complex, five-syllable utterance containing a one-syllable target word. Six between-subjects conditions were tested with 20 adult participants each. In condition 1, the only cue to word-meaning mapping was the co-occurrence of word and referents. This statistical cue was present in all conditions. In condition 2, the target word was sounded at a higher pitch. In condition 3, random one-syllable words were sounded at a higher pitch, creating an inconsistent cue. In condition 4, the duration of the target word was lengthened. In conditions 5 and 6, an extraneous acoustic cue and a visual cue were associated with the target word, respectively. Performance in this word-learning task was significantly higher than that observed with simple co-occurrence only when pitch prominence consistently marked the target word. We discuss implications for the intentional value of pitch marking as well as the relevance of our findings to language acquisition and language evolution.